1225. The Perfect Storm: A Hardy and Lethal Pathogen and a Unit Filled with Immunocompromised Patients with Large Open Wounds. Troubles with Candida Auris in a Burn Intensive Care Unit. (15th December 2022) - Moore, Riley; Lie, Louise; Pua, Herminia; Slade, David H; Rangel, Sharon; Davila, Anthony; Carson, Joshua S; Parada, Jorge Paiva
Abstract: Background: C auris is an emerging often multidrug resistant pathogen capable of causing severe morbidity and mortality. C auris has been increasingly isolated from patients in skilled nursing facilities and hospitals, and has been associated with facility outbreaks. A resilient pathogen, C. auris survives harsh disinfectants, desiccation and readily colonizes the environment posing an especially great risk to immunocompromised patients with large open wounds and long lengths of stay. Methods: From 7/1/21 - 8/30/21 we noted a cluster of 4 patients with C auris in clinical cultures from the Burn ICU (BICU). A multidisciplinary team involving infection prevention, nursing/medical directors, health and safety, engineering, environmental services, and hospital leadership investigated the cluster as a potential outbreak. Mitigation measures involved a multi-modal response of C auris admission screening, weekly point prevalence testing of all BICU patients, environmental surface cultures, enhanced room cleaning, staff education, hand hygiene and personal protective equipment usage audits. Results: 11 cases of C auris were identified on our BICU from 7/1/21 - 2/28/22. 5 (45.5%) cases from clinical isolates, 1 (9.1%) from a BICU point prevalence screen on 12/15/21, 5 (45.5%) as a part of weekly point prevalence screens started on 1/1/22. 6 (54.5%) patients were admitted for burn related injuries, 2 (18.2%) for Steven Johnson Syndrome, 2 (18.2%) for necrotizing wounds, and 1 (9.1%) for COVID-19 pneumonia. Cases occurred in 6/10 rooms in the Burn ICU. One (9.1%) patient expired during this outbreak (not deemed to be from C auris infection). Conclusion: Resilient infections like C auris pose a risk of nosocomial transmission and potential high morbidity and mortality to burn patients with impaired immune defense and large open wounds. A multidisciplinary team using targeted interventions including screening, education, enhanced cleaning eradicated the outbreak in our BICU. As of 5/1/22, we went 13 + weeks without identifying a new case. The last patient with C auris was discharged 3/16/22. To prevent future outbreaks, we created a standardized response plan and instituted a universal screening protocol for C auris targeting all patient admissions from skilled nursing facilities and admissions to all ICUs. Disclosures: Jorge Paiva Parada, MD MPH, Shionogi: Honoraria.